Recent advances on human mpox. (January 2023) - Orassay, Aliya; Berdigaliyev, Alan; Sadvokassova, Darya; Diassova, Ansal; Amin, Amr; Cao, Wenwen; Xie, Yingqiu
Abstract: Mpox has been a concern of public health and travel caution. Using databases of WHO, CDC, google scholar, and PubMed, we searched recent literatures and reviewed the history, genomic mutation/evolution, host cell response pathways, regulation policy, vaccine and therapy development. Recent studies showed that current mpox has many genomic mutations related to regulation by APOBEC3. Current mpox has also been suggested to be associated with sexual transmission. Vaccination should be applied and anti-mpox drug should be urgently developed. More investigations are needed to ensure outbreak prevention.